The formation of near anode double layer in highcurrent plasma diode of low pressure - Tseluyko, A.F.; Zinov’ev, D.V.; Borisko, V.N.; Tseluyko, V.A.; Drobishevskaya, A.A. (Вопросы атомной науки и техники, 2002)
A plasma electron source on the basis of a pulse plasma diode of low pressure with an extended interelectrode gap has been experimentally investigated. The basis of a plasma electron source serves a gas discharge of a new type - selfmaintained beam-plasma discharge, which distinctive feature is the forming of a double electrical layer of a space charge in a discharge gap and generation of an intensive electron beam. The exterior parameters were determined, at which formation of a double layer and the acceleration of an electron beam in such discharge occurs immediately at working area of the anode. The plasma electron source is calculated on generation of an electron beam with the energy 〖10〗^4…〖10〗^5 eV at the current 2…3 kA, current density 200…300 A/cm 2 , pulse length 1…10 μs and efficiency of conversion of an exterior electric field energy into an electron beam energy up to 80%.